2012
DOI: 10.1038/srep00295
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α and TGF-β Counter-Regulate PD-L1 Expression on Monocytes in Systemic Lupus Erythematosus

Abstract: Monocytes in patients with systemic lupus erythematosus (SLE) are hyperstimulatory for T lymphocytes. We previously found that the normal program for expression of a negative costimulatory molecule programmed death ligand-1 (PD-L1) is defective in SLE patients with active disease. Here, we investigated the mechanism for PD-L1 dysregulation on lupus monocytes. We found that PD-L1 expression on cultured SLE monocytes correlated with TNF-α expression. Exogenous TNF-α restored PD-L1 expression on lupus monocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 56 publications
9
56
2
Order By: Relevance
“…PD-L1 expression can be modulated by a number of cytokines, including type I and II IFNs, TNFa, and TGFb (16,23,(30)(31)(32). We show that tumor cell expression of PD-L1 can be enhanced following coculture with IFNg and that addition of TNFa can further augment this response.…”
Section: Discussionmentioning
confidence: 83%
“…PD-L1 expression can be modulated by a number of cytokines, including type I and II IFNs, TNFa, and TGFb (16,23,(30)(31)(32). We show that tumor cell expression of PD-L1 can be enhanced following coculture with IFNg and that addition of TNFa can further augment this response.…”
Section: Discussionmentioning
confidence: 83%
“…Peripheral blood mononuclear cells and plasma were isolated within 6 h and cryopreserved. PD-L1 expression assays were performed as previously reported (20,35). PD-L1 + cells segregated into monocyte (Mo: CD14 high CD11c + ), activated monocyte (aMo: CD14 + CD11c + CD16 + ), and immature myeloid dendritic cell (mDC: CD14 low CD11c + ) populations.…”
Section: Methodsmentioning
confidence: 99%
“…Ou et al reported that in SLE monocytes opposing actions of TNF-α and Transforming growth factor (TGF)-β regulated the expression of PD-L1 [74]. PD-L1 expression could be revived by exogenous TNF-α on lupus monocytes [74]. TGF-β has shown to inhibit PD-L1 expression on monocytes [74].…”
Section: Regulation Of Pd-l1mentioning
confidence: 99%
“…Enhanced expression of PD-L1 was present on immature dendritic cells (iDCs) after being treated with granulocyte-macrophage colony-stimulating factor (GM-CSF) [73]. Ou et al reported that in SLE monocytes opposing actions of TNF-α and Transforming growth factor (TGF)-β regulated the expression of PD-L1 [74]. PD-L1 expression could be revived by exogenous TNF-α on lupus monocytes [74].…”
Section: Regulation Of Pd-l1mentioning
confidence: 99%
See 1 more Smart Citation